2020
DOI: 10.1155/2020/3142918
|View full text |Cite
|
Sign up to set email alerts
|

First Age- and Gender-Matched Case-Control Study in Australia Examining the Possible Association between Toxoplasma gondii Infection and Type 2 Diabetes Mellitus: The Busselton Health Study

Abstract: An emerging field of research is starting to examine the association of infectious pathogens with type 2 diabetes mellitus (T2DM). An understudied parasite of interest is Toxoplasma gondii. Globally, very few studies have been conducted to investigate this association. Additionally, very little data exists on the prevalence of T. gondii in the general Australian population. Our group sought to determine the prevalence, association, and risk factors between T. gondii infection and T2DM from a representative Aus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
(39 reference statements)
1
5
0
Order By: Relevance
“…The high prevalence of toxoplasmosis in the sample population could not be concluded as an association between toxoplasmosis and T2DM in our study, as the rate of prevalence of the infection did not differ significantly between T2DM patients (39.39%) and healthy controls (39.73%). Similar results were observed in the studies on Mexican, Australian, and American populations [ 9 , 12 , 13 ]. Strain differences and geographical bias may lead to altering results from the studies conducted in Middle-East countries [ 14 – 16 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The high prevalence of toxoplasmosis in the sample population could not be concluded as an association between toxoplasmosis and T2DM in our study, as the rate of prevalence of the infection did not differ significantly between T2DM patients (39.39%) and healthy controls (39.73%). Similar results were observed in the studies on Mexican, Australian, and American populations [ 9 , 12 , 13 ]. Strain differences and geographical bias may lead to altering results from the studies conducted in Middle-East countries [ 14 – 16 ].…”
Section: Discussionsupporting
confidence: 90%
“…T. gondii infection is counted as one of the “Five Neglected Parasitic Infections” by the Centers for Disease Control [ 9 ]. The rate of this infection and the vulnerability to severe cases of the disease in humans largely depends on the strain availability in a certain geographical location as well as the host's immune responses to the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…This argument might be ascribed to genetic causes and racial susceptibility differences favoring the Middle East. 27 Single nucleotide polymorphism in proinflammatory mediators (such interleukin 1, TNF, and IFN-γ) and antiinflammatory cytokines (like Interleukin 10) might be a factor in this variance. 28,29 "The cytokine system's genetics have a significant impact on a person's chance of contracting or developing an infectious or autoimmune illness".…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence in Australia is not well-established, although a cross-sectional study in Western Australia found an overall seroprevalence for IgG to be 66%. 1 Felines are the only known definitive hosts. Oocysts are shed in the feces.…”
Section: Discussionmentioning
confidence: 99%
“…Toxoplasma gondii is a common parasite. The prevalence in Australia is not well‐established, although a cross‐sectional study in Western Australia found an overall seroprevalence for IgG to be 66% 1 …”
Section: Discussionmentioning
confidence: 99%